A New Prospective Solution to Meet the New Specifications Required on Agile Beam Antennas: ARMA Theory and Applications - Bernard Jecko; Pierre-Etienne Portalier; Mohamad Majed (Sensors)
The evolution of telecommunications and radars in the terrestrial and space domains is introducing new specifications for antennas that have difficulty meeting today’s phased arrays. Breakthrough technologies must be introduced to push back the limits not only in beam steering and beam forming, but also in frequency bandwidth, conformation, and multifunctionality. Indeed, the representation of radiating surfaces (Huygens) by arrays of point sources (a century ago!) is the poorest approximation of the rigorous solution, with well-known limitations. The proposed approach starts from the rigorous expression of the field radiated by any antenna obtained using the equivalence principle on any closed surface Sc surrounding the antenna. Important approximations are introduced to apply this rigorous result to the design of beam-agile multisource antennas that require sampling of the radiating Sc surface. The proposed approach samples the Sc surface by slicing it into small piecewise surfaces. For the fabrication of these small surfaces, structures called “pixels” deduced from the s have been designed. Many applications are proposed and compared with array solutions.